Duration and magnitude of faecal shedding of Shiga toxin-producing Escherichia coli from naturally infected cattle. - Widiasih, D. A. (Cambridge University Press, 2004)
To clarify the epidemiological relationship between cattle and human infections of Shiga toxin-producing Escherichia coli (STEC), we studied the duration and magnitude of the excretion of STEC O157 and STEC O26 with rectal faeces from naturally infected cattle at a breeding farm in the Tohoku area of Japan, using microbiological methods. The prevalence of STEC O157 was 3.5% (11/324), whereas that of STEC O26 was 7.9% (14/178). Faecal shedding of STEC O157 persisted for < 1 week to 10 weeks, whereas STEC O26 persisted from < 1 week to < 3 weeks. The magnitude of faecal shedding (per 10 g) ranged from 4 to > 110,000 c.f.u. for STEC O157 and from 3 to 2400 c.f.u. for STEC O26. All isolates of both STEC serotypes contained the stx1 or stx2 genes. Pulsed-field electrophoretic analysis of both STEC serotypes identified predominantly STEC O157 type III and STEC O26 type I in isolates, suggesting that a single STEC strain may be mutated in the intestinal tract of calves. These results indicate that STEC O157 is secreted for longer periods and in higher numbers than STEC O26 from healthy calves with natural infections, suggesting that STEC O157 may have more opportunities than STEC O26 to induce human disease.